Agri-environmental efficiency оf seeds processing of water extracts from rocks and vermikomposts - L P Stepanova; V N Starodubzev; E I Stepanova (RUDN Journal of Ecology and Life Safety, 2011)
Processing of seeds before crop of microelements increases yield and quality of the products. The use of organic and mineral substances contained in the vermikomposts and rock provide a positive impact on sown quality, growth and development of plants, their resistance to adverse factors and can be performed in households without additional financial costs for their acquisition аnd for utilization waste production in the region.